Small Nuclear RNAs (U1, U2, U5) in Tumor-Educated Platelets Are Downregulated and Act as Promising Biomarkers in Lung Cancer - Dong, Xiaohan; Ding, Shanshan; Yu, Miao; Niu, Limin; Xue, Linlin; Zhao, Yajing; Xie, Li; Song, Xingguo; Song, Xianrang (Frontiers in Oncology, 2020)
Background: Small nuclear RNA (snRNA) levels are extremely variable across a wide range of biological conditions. SnRNAs could potentially regulate alternative splicing to drive genetic, dysplastic and neoplastic disease, which might be the main reason for mRNA profile alteration in tumor educated platelets (TEPs). Methods: Platelets were isolated from the plasma of lung cancer patients and healthy donors by low-speed centrifugation and subjected to RNA isolation. SnRNA U1, U2, U5 levels were detected by quantitative real-time polymerase chain reaction (qRT-PCR). Exosomes were isolated by ultracentrifugation and identified by qNano. Results: TEP U1, U2, U5 levels were significantly decreased in patients with lung cancer as well as with early-stage patients, their downregulation was correlated with lung cancer progression, processing favorable diagnostic efficiency. More importantly, TEP U1, U2 and U5 levels were closely correlated between paired exosomes and TEP from treated patients but not from untreated ones, and U1, U5 but not U2 in platelets were elevated by apo-exosomes. Conclusions: Tumor educated platelet small nuclear RNAs are downregulated and act as promising biomarkers in lung cancer.